EFFECT OF MOBILE MONEY MERCHANTS SERVICES ON FINANCIAL PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN SELECTED WARDS IN NAKURU CITY - NJUGUNA, EDWARD WAITHAKA (Kabarak University, 2023)
Mobile money has become a popular payment method for many Kenyan businesses. The goal of this study was to determine how mobile money merchant services affected the financial performance of small and medium-sized businesses. Nakuru is a city in Kenya. The specific goals were to determine the effect of affordability of mobile money merchant services on the performance of small and medium enterprises, the effect of availability of mobile money merchant services on the performance of small and medium enterprises, the effect of effectiveness of mobile money merchant services on the performance of small and medium enterprises, and the impact of Value Added Services available on mobile money platforms on the performance of small and medium enterprises. The theories underpinning the study were; Technology Acceptance Model and Innovation Diffusion Theory (IDT). The study adopted explanatory survey design based on cause-effect relationship. The study targeted 12,250 licensed SMEs Mobile Money Merchants operating in Nakuru City. The study sampled 221 Small and Medium Mobile Money Merchant enterprises using stratified sampling technique. Small and Medium Enterprises in Nakuru City were chosen using simple random sampling. The study relied on primary data gathered through structured questionnaires as the primary data collection tool. The data was analyzed using regression analysis technique. The information was then presented in the form of frequency tables and figures. The study established that the effectiveness of Mobile Money Merchant Services had no effect on the financial performance of Kenyan Small and Medium Enterprises. Mobile Money services, according to the study, are becoming increasingly popular in many countries as a convenient, secure, and cost-effective way to make payments and transfers. The study recommends that the governments should create and enforce legislation that regulates and safeguards the use of Mobile Money services in order to ensure their safety and security.
Keywords: Mobile Money Services; Value Added Services; Small and Medium Enterprises; Mobile Money Services; Financial Performance